2021
DOI: 10.2166/aqua.2021.056
|View full text |Cite
|
Sign up to set email alerts
|

Defining domestic water consumption based on personal water use activities

Abstract: As the world increasingly faces water shortages, it is critical to develop realistic estimates of water consumption based on water-use activities rather than top-down imposed limits. This study quantifies the absolute basic consumption (ABC) of an individual, irrespective of water-use location or water source, with a focus on personal water-use activities rather than measured household consumption. A theoretical model to stochastically describe 21 personal water-use activities was developed, corresponding to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 19 publications
1
26
0
1
Order By: Relevance
“…Reducing water use through demand management strategies without compromising consumer service or severely influencing healthy, sustainable urban living poses a significant challenge to sustainable cities (Crouch et al 2021 ). A variety of ranges have been reported for the required liters per capita per day (LPCD) from between 20 and 50 LPCD (Howard et al 2003 ) to between 40 and 509 LPCD (Athuraliya et al 2012 ; Biswas and Gangwar 2021 ; Hay et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing water use through demand management strategies without compromising consumer service or severely influencing healthy, sustainable urban living poses a significant challenge to sustainable cities (Crouch et al 2021 ). A variety of ranges have been reported for the required liters per capita per day (LPCD) from between 20 and 50 LPCD (Howard et al 2003 ) to between 40 and 509 LPCD (Athuraliya et al 2012 ; Biswas and Gangwar 2021 ; Hay et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of ranges have been reported for the required liters per capita per day (LPCD) from between 20 and 50 LPCD (Howard et al 2003 ) to between 40 and 509 LPCD (Athuraliya et al 2012 ; Biswas and Gangwar 2021 ; Hay et al 2012 ). Such an extensive range shows its dependency on various factors such as the type of household water use, the efficiency of urban service, local climate, and building preferences (Crouch et al 2021 ). Prior to the COVID-19 epidemic, studies revealed that investment in network maintenance is the most essential method to save water, followed by legislation, individual meters, and public campaigns advocating for the adoption of water-saving devices and water conservation behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the items engage in activities to carefully make them in order to satisfy the wants and expectations of the customers. The system has evolved through time and can now support the company's strategic vision by recognizing its strengths, weaknesses, and feasible prospects that add up or do not add up, therefore reflecting the organizational dynamics that affect costs with greater precision (Hansen et al, 2021;Crouch et al, 2021;Haroun, 2015). Traditional management control systems have come under fire in recent years for failing to fulfill modern social demands and provide services for overall organizational growth.…”
Section: Introductionmentioning
confidence: 99%
“…The crucial aspect of overall water scarcity that has the greatest impact on people is domestic water scarcity (DWS), or the lack of safe and sufficient water for household needs (Crouch et al, 2021;Strauch et al, 2021). According to several research studies, the absence of sufficient and clean water for various uses led to a total human quality of life reduction by restricting diverse wellness and escalating health issues (Shrestha et al, 2018;Sudsandee et al, 2022).…”
Section: Introductionmentioning
confidence: 99%